معاينة مدى تطبيق ابعاد الشمول المالي في المصارف التجارية الليبية من وجهة نظر عملائها: ((دراسة ميدانية)) (Comprehensive Journal of Science, 2025)
This study aims to determine the extent of the response of the surveyed sample towards the application of the dimensions of financial inclusion in Libyan commercial banks. To achieve this goal, a field study was conducted on the customers of Libyan commercial banks. Due to the difficulty of enumerating all the elements of the study population, which is one of the unbounded populations whose elements are difficult to enumerate, and also because the study population is characterized by homogeneity, a simple random sample was used. Consequently, an electronic questionnaire was prepared, and (170) responses were obtained to the electronic questionnaire, which was specifically prepared to answer the questionnaire items. Its validity and reliability coefficient were confirmed. The study reached a number of results, the most important of which is that there is an application of the dimensions of financial inclusion in Libyan commercial banks.